Are physical performance and injury risk in a professional soccer team in match-play affected over a prolonged period of fixture congestion? - Carling, C.; Le Gall, F.; Dupont, G. (International Journal of Sports Medicine, 2012)
In this study, the effects of a prolonged period of fixture congestion (8 successive official matches in 26 days) on physical performance and injury risk and severity in a professional soccer team were investigated. Computerised motion-analysis was used to analyse the overall distance covered and that run at light- (0.0-11.0 km/h); low- (11.1-14.0 km/h); moderate- (14.1-19.7 km/h) and high-intensities (>/=19.8 km·h - 1) for the team as a whole. Distances were measured in metres per minute. Information on match injuries was recorded prospectively. The overall distance covered varied across successive matches (p<0.001) as more distance was run in games 4 and 7 compared to 2 and 3, respectively (126.6±12.3 m/min and 125.0±13.2 m/min vs. 116.0±8.0 m/min and 115.5±11.0 m/min). Distance run in light-intensity exercise also varied (p<0.001) as more distance was covered in game 4 vs. 1, 2, 3, 5 and 6 (75.5±3.8 m/min vs. 70.6±2.4 m/min, 71.8±3.4 m/min, 69.3±2.6 m/min, 71.5±3.1 m/min, and 70.3±2.8 m/min) and in game 8 vs. game 3 (73.1±3.8 vs. 69.3±2.6 m/min), respectively. When comparing match halves, there were no differences across games in overall or high-intensity distance covered and performance in these measures was similar for matches played before, during and after this period. Globally, no difference over the 8 games combined was observed between the reference team and opponents in any of the performance measures whereas the overall distance covered and that in low- (both p<0.001) and high-intensity running (p=0.040) differed in individual games. The incidence of match injury during the congested fixture period was similar to rates reported outside this period but the mean lay-off duration of injuries was substantially shorter during the former (p<0.05). In summary, while the overall distance run and that covered at lower intensities varied across games, high-intensity running performance and injury risk were generally unaffected during a prolonged period of fixture congestion. These results might be linked to squad rotation and post-match recovery strategies in place at the present club.